2010
DOI: 10.1099/mic.0.040626-0
|View full text |Cite
|
Sign up to set email alerts
|

The type III secretion system of Vibrio alginolyticus induces rapid apoptosis, cell rounding and osmotic lysis of fish cells

Abstract: Vibrio alginolyticus is a Gram-negative bacterium and has been recognized as an opportunistic pathogen in humans as well as marine animals. However, the virulence mechanisms for this species of Vibrio have not been elucidated. This study characterized multiple mechanisms that induce cell death in fish cells upon infection with a V. alginolyticus strain, ZJO. The bacterium required its type III secretion system (T3SS) to cause rapid death of infected fish cells. Dying cells exhibited some features of apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…VscC is a structural protein that is required for a functional T3SS in V. alginolyticus (Zhao et al, 2010). When vscC was knocked out and exsE was expressed in trans (Δ vscC :p exsE ), ExsE was not detected in the supernatant (Figure 5, lane 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VscC is a structural protein that is required for a functional T3SS in V. alginolyticus (Zhao et al, 2010). When vscC was knocked out and exsE was expressed in trans (Δ vscC :p exsE ), ExsE was not detected in the supernatant (Figure 5, lane 6).…”
Section: Resultsmentioning
confidence: 99%
“…V. alginolyticus is prevalent in coastal waters of southern China and it is commonly associated with costly disease of aquatic animals (Austin, 2010). Previous studies demonstrated that V. alginolyticus induces apoptosis, cell rounding and osmotic lysis in fish cells and autophagy in mammalian cell lines in a T3SS-dependent manner (Zhao et al, 2010, 2011). Although the T3SS of V. alginolyticus is similar to T3SS1 of V. parahaemolyticus with respect to gene synteny (Zhao et al, 2010), it is unclear if the same regulatory mechanism is employed by V. alginolyticus .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pNA light emission was quantified on a TECAN Infinite 200 plate reader at 405 nm. The assay was performed as described previously [20].…”
Section: Primer Namementioning
confidence: 99%
“…Infection experiments in fish showed that the eseD mutant exhibited slower proliferation and a 10-fold decrease in virulence in fish (Wang et al, 2010a). Finally, in V. alginolyticus, a type III secretion system (T3SS) is required to cause rapid death of infected carp fish cells (Zhao et al, 2010).…”
Section: Protein Secretion Systemsmentioning
confidence: 99%